2017
DOI: 10.1039/c7nr00930e
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled nitrogen-doped fullerenes and their catalysis for fuel cell and rechargeable metal–air battery applications

Abstract: In this study, we report self-assembled nitrogen-doped fullerenes (N-fullerene) as non-precious catalysts, which are active for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), and thus applicable for energy conversion and storage devices such as fuel cells and metal-air battery systems. We screen the best N-fullerene catalyst at the nitrogen doping level of 10 at%, not at the previously known doping level of 5 or 20 at% for graphene. We identify that the compressive surface strain indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Therefore, GNR might not be suitable as a support material because it is imperatively vulnerable to carbon corrosion. Recently, heteroatom-doped carbon-based support materials such as nitrogen, sulfur, boron, phosphorous, and uorine [24][25][26][27][28][29][30][31] were studied to improve the intrinsic properties of catalytic activities and electrochemical durability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, GNR might not be suitable as a support material because it is imperatively vulnerable to carbon corrosion. Recently, heteroatom-doped carbon-based support materials such as nitrogen, sulfur, boron, phosphorous, and uorine [24][25][26][27][28][29][30][31] were studied to improve the intrinsic properties of catalytic activities and electrochemical durability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the durability of nanoscale carbon supports is an important issue in terms of long-term stability. The H 2 O and O adsorption strengths, which indicate thermodynamic stability, are important factors for the corrosion durability of the carbon support 38 . Comparing the binding energies of H 2 O and O with support materials would provide a good guide for investigating the corrosion durability of the carbon support.…”
Section: Introductionmentioning
confidence: 99%
“…Among different kinds of electrode materials, nanostructured carbon materials have represented the most promising and challenging materials since their extensive applications in the realm of electrochemistry . Several of carbon materials like carbon nanotubes (CNTs), fullerene, and graphene have been applied as the anodes in LIBs due to their superior electronic conductivity, structural stability, light weight, and flexibility compared with other metal and oxide anodes . However, the carbon atom arrangements in these nanosize carbon materials are the same as the commercial graphite anode, which is composed of all sp 2 ‐hybridized carbon atoms, indicating the similarly limited Li + storage mechanism by situating Li + between the carbon sheets …”
Section: Introductionmentioning
confidence: 99%
“…First-principles density functional theory (DFT) calculations have revealed that self-assembled N-doped (10 at%) fullerene would be efficient for OER performance because of their optimized binding energy for reaction intermediates. [92] The possibility of tuning the binding energy through the surface strain effect induced by controlling the N-doping level has also been demonstrated. It was found that the compressive surface strain induced by N dopants played a key role in finetuning of catalytic activities.…”
Section: Carbon-based Catalysts For Oermentioning
confidence: 99%